Hubungan Kesiapan Mandiri, Kreativitas Belajar dan Motivasi terhadap Kemampuan Pemecahan Masalah - Mohammad Amin Lasaiba; Arman Man Arfa (SAP (Susunan Artikel Pendidikan), 2023)
In an increasing digital era, problem-solving skills have become a crucial skill that every student needs in their learning activities. However, there are still various difficulties in developing these skills due to several influential factors. Self-readiness, learning creativity, and learning motivation that affect problem-solving abilities are the focus of this study. This study is based on a quantitative approach and conducted on students in grade X at SMA Negeri 13 Ambon in 2022. Samples were obtained using purposive sampling and tests and questionnaires were applied to obtain data, which was then processed using the SMARTPLS 4 application. The results of the study showed that the outer model testing, loading factor values, and Cronbach's Alpha were above 0.7, indicating relatively high validity and reliability. The inner model (R-square 0.546) indicated that 54.6% of the dependent variable could be explained by the predictor variables of self-readiness, motivation, and learning creativity. Hypothesis testing showed that there was a significant positive influence between the predictor variables of self-readiness and motivation, with T-statistic > 1.96 and a p-value of 0.05 (5%). However, one variable, which is learning creativity, did not have a significant effect.